Impact Produced by Recrystallization of Mechanically Destroyed Layer on Planar Side of Silicon Wafer Upon Electrical Parameters of CMOS Microcircuits - U. A. Pilipenka; V. A. Saladukha; H. A. Siarheichyk; D. U. Shestouski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2024)
The influence of recrystallization of a mechanically damaged layer on the working side of a silicon wafer using rapid heat treatment (1000 °C, 20 s) on the electrical parameters of complementary metal-oxide-semiconductor microcircuits has been established. The analyzed characteristics of  n- and  p-channel transistors were selected: drain current from the gate voltage when diode-connected; output characteristics at various gate voltages; drain current from the drain voltage without applying potential to the gate; percentage of yield of suitable products. These parameters were compared with microcircuits manufactured using standard technology. Analysis of  the results showed that rapid thermal treatment of the original silicon wafers can significantly improve the above characteristics  of  n-channel  metal-oxide-semiconductor  ( n-MOS)  and  p-channel  metal-oxide-semiconductor (p-MOS) transistors by reducing the fixed charge in gate dielectric obtained by pyrogenic oxidation of silicon. This makes it possible to improve the quality of manufactured complementary metal-oxide-semiconductor  microcircuits and  increase the percentage of yield of suitable products from 74.38 to 77.53 %.